Minimal Multiple Blocking Sets - Bishnoi, Anurag; Mattheus, Sam; Schillewaert, Jeroen (The Electronic Journal of Combinatorics, 2018)
We prove that a minimal t-fold blocking set in a finite projective plane of order n has cardinality at most \[12 n4tn - (3t + 1)(t - 1) + 12 (t - 1)n + t.\] This is the first general upper bound on the size of minimal t-fold blocking sets in finite projective planes and it generalizes the classical result of Bruen and Thas on minimal blocking sets. From the proof it directly follows that if equality occurs in this bound then every line intersects the blocking set S in either t points or 12(4tn - (3t + 1)(t - 1) + t - 1) + 1 points. We use this to show that for n a prime power, equality can occur in our bound in exactly one of the following three cases: (a) t = 1, n is a square and S is a unital; (b) t = n - n, n is a square and S is the complement of a Baer subplane; (c) t = n and S is equal to the set of all points except one. For a square prime power q and t ≤ q + 1, we give a construction of a minimal t-fold blocking set S in PG(2,q) with |S| = qq + 1 + (t - 1)(q - q + 1). Furthermore, we obtain an upper bound on the size of minimal blocking sets in symmetric 2-designs and use it to give new proofs of other known results regarding tangency sets in higher dimensional finite projective spaces. We also discuss further generalizations of our bound. In our proofs we use an incidence bound on combinatorial designs which follows from applying the expander mixing lemma to the incidence graph of these designs.